If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -6x + -8 = -15 + -4x Reorder the terms: 5 + -8 + -6x = -15 + -4x Combine like terms: 5 + -8 = -3 -3 + -6x = -15 + -4x Solving -3 + -6x = -15 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -3 + -6x + 4x = -15 + -4x + 4x Combine like terms: -6x + 4x = -2x -3 + -2x = -15 + -4x + 4x Combine like terms: -4x + 4x = 0 -3 + -2x = -15 + 0 -3 + -2x = -15 Add '3' to each side of the equation. -3 + 3 + -2x = -15 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = -15 + 3 -2x = -15 + 3 Combine like terms: -15 + 3 = -12 -2x = -12 Divide each side by '-2'. x = 6 Simplifying x = 6
| -10=x+21 | | 4+(5*0.25)= | | 5x-x+10=0 | | 8x+10=6(8x) | | 3k+2k=2+6k | | (x*0.75)+(5*0.25)=4 | | -2x^2-3x+54=0 | | -2x-3x+54=0 | | -3+7k=1+8k | | Cos(x)+7x=0 | | 100x^2-x-10=0 | | 54=89-36y | | m+599.01=686.98 | | -12c^2-38c=-40 | | c-19.2=24.0 | | 11-8n=1-6n | | 7x+3x=77 | | a-108.8=-203.0 | | r^2+3-2=0 | | x^2+nx+3x+3n=0 | | 2x^2-3-5=0 | | m+19.32=23.86 | | x=3(13/12-4) | | 8x+2=7(x-3)+4 | | x^2-dx-cx+dc=0 | | -6+m=-3m+6m | | 2p-6=-12+8p | | 3-6v+6v=15+3v | | 30+4x=6x-35 | | 9x*-12x+4=0 | | -1(x-6)=8x-12 | | 8p-28=-22+9p |